ОБ’ЄДНАННЯ КОМУНАЛЬНИХ НЕКОМЕРЦІЙНИХ ПІДПРИЄМСТВ ЯК ВАЖЛИВИЙ КОМПОНЕНТ КЛАСТЕРНОГО ПІДХОДУ В ОРГАНІЗАЦІЇ СИСТЕМИ ОХОРОНИ ЗДОРОВ’Я ТЕРИТОРІАЛЬНИХ ГРОМАД (ІННОВАЦІЙНА ЕКОНОМІКА, 2022)
Паненко В.В., Поліщук О.Т. ОБ’ЄДНАННЯ КОМУНАЛЬНИХ НЕКОМЕРЦІЙНИХ ПІДПРИЄМСТВ ЯК ВАЖЛИВИЙ КОМПОНЕНТ КЛАСТЕРНОГО ПІДХОДУ В ОРГАНІЗАЦІЇ СИСТЕМИ ОХОРОНИ ЗДОРОВ’Я ТЕРИТОРІАЛЬНИХ ГРОМАДМета. Обґрунтування теоретико-методичної основи формування кластерних об’єднань у системі охорони здоров’я територіальних громад та надання практичних рекомендацій щодо їх функціонування, на тлі різноманітних форм організації та сукупності відносин, які виникають в рамках кластерного об’єднання в умовах децентралізації повноважень.Методика дослідження. Методичною основою дослідження є системний та інституціональний підходи, згідно із якими всі процеси управління системою охорони здоров’я територіальної громади відповідають чинному законодавству. Використано наступні методи: структурно-функціонального дослідження – для аналізу основних тенденцій соціально-економічної ситуації розвитку; статистичних порівнянь – для оцінки впливу медичної галузі на регіональний розвиток. Узагальнення методичних підходів розвинених країн щодо формування системи кластерного управління показало, що регіональна система охорони здоров’я здатна функціонувати ефективно за умови врахування прийнятих управлінських рішень і отриманих від їх реалізації результатів, що відбивається в оцінці її стану на відповідних етапах розвитку.Результати дослідження. Обґрунтовано, що ефективність регулювання сфери охорони здоров’я в сучасних умовах значною мірою залежить від забезпечення доступу всіх учасників соціально-економічних відносин в сфері охорони здоров’я до необхідних ресурсів. Регулювання необхідно спрямовувати на забезпечення реалізації потенціалу сфери охорони здоров’я на основі максимально ефективного використання її ресурсів.Встановлено, що одним із найбільш оптимальних інструментів інтеграції інтересів влади, бізнесу і населення в цій сфері є так званий «кластерний підхід», зважаючи на його універсальні механізми, високу ефективність застосування і простоту організації. Територіальні кластери є діючою силою економічного розвитку і потужним інструментом взаємозв’язків між учасниками регіональних інноваційних систем у різних країнах світу.Доведено, що кластер дає важливі синергетичні ефекти, без яких сучасне життя неможливе, він є способом мобілізації можливостей зацікавлених сторін (держави, бізнесу, наукового співтовариства) і інструментом формування науково-технічної і інноваційної політики для досягнення кінцевої мети у напрямі інноваційного розвитку і технологічної модернізації економіки в сфері медицини, фармацевтики і супутніх галузях економіки.З’ясовано, що корпорація комунальних некомерційних підприємств системи охорони здоров’я виконує роль активного комунікатора і інтегратора для учасників майбутнього медичного кластера та організацій сфери охорони здоров’я. В перспективі таке об’єднання стане міжнародним центром комунікацій і обміну компетенціями, а запуск порталу про медичні технології і інновації в охороні здоров’я – дозволить транслювати цей позитивний досвід в маси, розповідати про досягнення в медицині.Систематизовано ознаки господарських об’єднань (корпорації). Встановлено, що це – складна організація, яка створена на основі поєднання матеріальних інтересів підприємств-учасників, діє на підставі установчого договору або статуту як юридична особа.Сформовано переваги об’єднання підприємств у сфері охорони здоров’я, а саме: об’єднання комунальних некомерційних підприємств. Основні з них, це ефективне використання кадрового потенціалу, матеріально-технічної бази, покращення медичних послуг для пацієнтів.Наукова новизна результатів дослідження. Запропоновано створення корпорації комунальних некомерційних підприємств у системі охорони здоров’я територіальної громади, що, на відміну від існуючого, дозволить оптимально й ефективно використовувати наявні ресурси, генерувати інноваційні рішення та створить передумови для взаємодії усіх учасників медичного сектора. Вперше запропоновано, після реалізації проєкту щодо створення корпорації, яка об’єднає некомерційні підприємства медичної сфери в горизонтально-інтегровану структуру, на її платформі створити повноцінний медичний кластер територіальної громади. Корпорація трансформується в управляючу компанію регіонального медичного кластеру, основні функції якої будуть зводитись до загальної координації роботи кластеру та управлінню проєктами.Практична значущість результатів дослідження. Розроблено конкретні рекомендації щодо створення корпорації – об’єднання комунальних некомерційних підприємств, із чіткою стратегією, комплексною методикою та сформованою дорожньою картою, як складової повноцінного медичного кластеру територіальної громади.Ключові слова: охорона здоров’я; кластер; територіальна громада; корпорація; комунальне підприємство; некомерційне підприємство. Panenko V.V., Polishchuk O.T. ASSOCIATION OF MUNICIPAL NON-PROFIT ENTERPRISES AS AN IMPORTANT COMPONENT OF THE CLUSTER APPROACH IN THE ORGANIZATION OF THE HEALTHCARE SYSTEM OF TERRITORIAL COMMUNITIESPurpose. The aim of the article is to substantiate the theoretical and methodological basis for the formation of cluster associations in the healthcare system of territorial communities, against the background of various forms of organization and set of relations that arise within the cluster association in the context of decentralization of powers.Methodology of research. The methodological basis of the study is the systemic and institutional approaches, according to which all processes of management of the health care system of the local community comply with current legislation. The following methods were used: structural and functional research – to analyse the main trends of the social and economic situation of development; statistical comparisons – to assess the impact of the medical industry on regional development. The generalization of methodological approaches of developed countries to the formation of a cluster management system has shown that the regional healthcare system is able to function effectively considering management decisions and the results obtained from their implementation, which is reflected in assessing its condition at the appropriate stages of development.Findings. It is substantiated that the effectiveness of healthcare regulation in modern conditions largely depends on ensuring access of all participants in social and economic relations in the field of healthcare to the necessary resources. Regulation needs to focus on realizing the potential of the health sector through the most efficient use of its resources.It is found that one of the most optimal tools for integrating the interests of government, business and the population in this area is the so-called “cluster approach” given its universal mechanisms, high efficiency, and simplicity of organization. Territorial clusters are an active force in economic development and a powerful tool for networking between participants in regional innovation systems in different countries of the world.It is proved that the cluster provides important synergetic effects, without which modern life is impossible, it is a way to mobilize stakeholders (state, business, scientific community) and a tool for science, technology, and innovation policy to achieve the goal of innovative development and technological modernization of the economy in medicine, pharmaceuticals and related industries.It is revealed that the corporation of communal non-profit enterprises of the health care system acts as an active communicator and integrator for the participants of the future medical cluster and health care organizations. In the future, such an association will become an international center of communication and exchange of competencies, and the launch of a portal on medical technology and innovation in healthcare – will broadcast this positive experience to the masses, talk about advances in medicine.The features of business associations (corporations) are systematized. It is established that this is a complex organization, which is created based on a combination of material interests of the participating enterprises, operates on the basis of the memorandum or articles of association as a legal entity.The advantages of merging enterprises in the field of healthcare are formed, namely: merging of communal non-profit enterprises. The main ones are the effective use of human resources, material and technical base, improvement of medical services for patients.Originality. It is proposed to create a corporation of public non-profit enterprises in the healthcare system of the local community, which, unlike the existing one, will allow optimal and efficient use of available resources, generate innovative solutions, and create preconditions for interaction of all medical sector participants.For the first time, after the implementation of the project to create a corporation that will unite non-profit medical enterprises into a horizontally integrated structure, it is proposed to create a full-fledged medical cluster of the territorial community on its platform. The corporation is being transformed into a management company of the regional medical cluster, the main functions of which will be reduced to the general coordination of the cluster’s work and project management.Practical value. Specific recommendations have been developed for the establishment of a corporation – the association of communal non-profit enterprises, with a clear strategy, comprehensive methodology and a formed road map, as part of a full-fledged medical cluster of the territorial community.Key words: healthcare; cluster; territorial community; corporation; municipal enterprise; non-profitenterprise.